Morphology of Garut City: Spatial Planning and Transportation System. (30th December 2020) - Sofianto, Kunto; Nugrahanto, Widyo; Yuniadi, Agusmanon; Falah, Miftahul
This paper examines the morphological growth of Garut City in historical perspective. To achieve this goal, this study used a historical method that includes four stages, namely heuristics, criticism, interpretation, and historiography. Garut city has been known as a tourist destination since the Dutch colonialism and became the main residential area of Europeans living on the island due to the existence of plantations in the South Garut region. These conditions make Garut City an urban area that has special features compared to other urban areas in Garut Regency. This study aims at addressing the following question: 1) How does the population influence the physical changes (morphology) of Garut City? 2) How was the railroad construction in Garut City during the Dutch colonial period? And 3) How is the influence of cosmology on the spatial layout of Garut City? The purpose of this study is to analyze the effect of population growth on the physical changes (morphology) of Garut city. The study seeks to explain the road traffic of Garut City and the factors that influenced spatial planning. The results showed that Kota Intan was the early name for Garut City, the center of government, economy, education, social, and culture of Garut Regency. The results also revealed that despite its rapid and dynamic morphological growth, Garut City still shows some traditional and colonial characteristics. Although its ancient road network is made in a way that does not interfere with the activity or movement of goods and services, its high population growth and development inequality prevent it from running properly.